The express registration of thermal conductivity anomalies of solids - Sokolenko, V.I.; Frolov, V.А.; Savchuk, E.S. (Вопросы атомной науки и техники, 2022)
Investigation of the thermophysical characteristics of materials at low temperatures (T ≤ Θ, Θ is the Debye temperature) makes it possible to obtain information on the interaction of quasiparticles and is in demand in the applied plan. For the indicated temperatures, a method of express registration (ER) of anomalies in the thermal conductivity of solids (k), which is a variation of the classical method of uniaxial stationary heat flux (USHF), but which, unlike the prototype, does not require taking into account heat losses (HL). A feature of the ER method is the measurement of the temperature dependence of the difference δΤ = T₁−T₂ between the ends of the sample under conditions of simultaneous monotonicity of the change in Т of the sample and all HL. In this case, the measured scaled thermal conductivity Ҝ∝(Q/Ψ)/δΤ (Ψ is a monotonic scale factor in T) correlates with the real k∝Q/δΤ. For the interval 300…77 K, one of the variants of the ER method was tested, in which a step-by-step movement of the sample in a column of gaseous nitrogen above the surface of liquid N₂ in a Dewar vessel was used. In the case of a monotonic change in the distance from the sample to the liquid, the formed configuration of isotherms ensures the monotonicity of the change in T of the sample and, at the same time, the monotonicity of the HL along the channels of thermal conductivity and radiation. The possibilities of the ER method are illustrated by examples of determining the temperatures and signs of anomalies in the thermal conductivity coefficients of high-temperature superconductors (HTSC) in the pseudogap state (PGS) and a high-entropy alloy Аl₀.₅CoCuCrNiFе, which is promising for use in the cryogenic temperature range. The method made it possible for the first time to discover the staging of the temperature evolution of the thermal conductivity of YBa₂Cu₃O₇₋ₓ and Bi₁.₆(Pb₀.₄)Sr₂Ca₂Cu₃O₁₀₊ₓ in the PGS and to determine the temperatures and signs of the anomalies. The data obtained convincingly confirmed the results of probing the PGS of HTSCs by the method of polarized neutron scattering carried out with the participation of a number of EU research institutes. Also, for the first time, an extended thermal conductivity anomaly of a high-entropy Аl₀.₅CoCuCrNiFе alloy in the range of ~ 220…170 K was discovered, which is probably a consequence of changes in the configuration of the Fermi surface. Дослідження теплофізичних характеристик матеріалів в області низьких температур (T ≤ Θ, Θ – температура Дебая) дає можливість отримувати інформацію про взаємодію квазічастинок і є затребуване у прикладному плані. Для вказаних температур запропоновано метод експрес-реєстрації (ЕР) аномалій коефіцієнта теплопровідності твердих тіл (k), що є різновидністю класичного методу одновісного стаціонарного теплового потоку (ОСТП), який не потребує, на відміну від прототипу, урахування теплових втрат (ТВ). Особливістю методу ЕР є вимір різниці δΤ = T₁−T₂ між кінцями зразка в умовах одночасної монотонності змін Т зразка і величин всіх ТВ. У цьому випадку вимірюваний масштабований коефіцієнт теплопровідності Ҝ∝(Q/Ψ)/δΤ корелює з реальним коефіцієнтом теплопровідності k∝Q/δΤ(Ψ – монотонний за Т коефіцієнт масштабу). Для інтервалу 300…77 К апробовано один з варіантів методу ЕР, в якому використовується покрокове переміщення зразка в стовпі газової фази над поверхнею рідкого азоту в посудині Дьюара. У разі монотонної зміни відстані від зразка до рідкого холодоагенту сформована конфігурація ізотерм забезпечує монотонність змін температури зразка і водночас – монотонність ТВ по каналах теплопровідності і випромінювання. Можливості ЕР проілюстровані прикладами визначення температур і знаків аномалій коефіцієнтів теплопровідності високотемпературних надпровідників (ВТНП) у псевдощілинному стані (ПЩС) і перспективного для використання в царині криогенних температур високоентропійного сплаву Аl₀.₅CoCuCrNiFе. Метод дозволив вперше виявити стадійність температурної еволюції теплопровідності ВТНП YBa₂Cu₃O₇₋ₓ і Bi₁.₆(Pb₀.₄)Sr₂Ca₂Cu₃O₁₀₊ₓ у ПЩС, а також встановити температури i знаки аномалій. Отримані дані переконливо підтвердили результати зондувань ПЩС ВТНП методом розсіювання поляризованих нейтронів, проведених за участю ряду дослідницьких інститутів ЄС. Також уперше виявлено протяжну аномалію теплопровідності високоентропійного сплаву Аl₀.₅CoCuCrNiFе в інтервалі ~ 220…170 K, що, вірогідно, є наслідком змін конфігурації поверхні Фермі. Исследование теплофизических характеристик материалов в области низких температур (T ≤ Θ, Θ – температура Дебая) дает возможность получать информацию о взаимодействии квазичастиц и востребовано в прикладном плане. Для указанных температур предложен метод экспресс-регистрации (ЭР) аномалий коэффициента теплопроводности твердых тел (k), являющийся разновидностью классического метода одноосного стационарного теплового потока (ОСТП), но который, в отличие от прототипа, не требует учета тепловых потерь (ТП). Особенностью метода ЭР является измерение температурной зависимости разности δΤ = T₁−T₂ между концами образца в условиях одновременной монотонности изменения Т образца и всех ТП. В этом случае измеряемый масштабированный коэффициент теплопроводности Ҝ∝(Q/Ψ)/δΤ коррелирует с реальным k∝Q/δΤ(Ψ – монотонный по Т коэффициент масштаба). Для интервала 300…77 К апробирован один из вариантов метода ЭР, в котором используется пошаговое перемещение образца в столбе газообразного азота над поверхностью жидкого N₂ в сосуде Дьюара. В случае монотонного изменения расстояния от образца до жидкости сформировавшаяся конфигурация изотерм обеспечивает монотонность изменения Т образца и одновременно – монотонность ТП по каналам теплопроводности и излучения. Возможности метода ЭР проиллюстрированы примерами определения температур и знаков аномалий коэффициентов теплопроводности высокотемпературных сверхпроводников (ВТСП) в псевдощелевом состоянии (ПЩС) и перспективного для применения в области криогенных температур высокоэнтропийного сплава Аl₀.₅CoCuCrNiFе. Метод позволил впервые обнаружить стадийность температурной эволюции теплопроводности ВТСП YBa₂Cu₃O₇₋ₓ и Bi₁.₆(Pb₀.₄)Sr₂Ca₂Cu₃O₁₀₊ₓ в ПЩС и определить температуры и знаки аномалий. Полученные данные убедительно подтвердили результаты зондирований ПЩС ВТСП методом рассеяния поляризованных нейтронов, проведенных с участием ряда исследовательских институтов ЕС. Также впервые обнаружена протяженная аномалия теплопроводности высокоэнтропийного сплава Аl₀.₅CoCuCrNiFе в интервале ~ 220…170 K, являющаяся, вероятно, следствием изменений конфигурации поверхности Ферми.